The Effect of Environment Analogy-Based Discovery Learning to Improve Students’ Environment Literacy and Understanding on Thermochemistry - Florida Doloksaribu; Irwandi Yogo Suaka; Catur Fathonah Djarwo (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
Abstract: The Effect of Environment Analogy-Based Discovery Learning to Improve Students’ Environment Literacy and Understanding on Thermochemistry. This research is the result of the implementation of thermochemistry learning based on the reconstruction of the analogy environment-based discovery learning model (DLBAE). The purpose of this study was to determine the effectiveness of the DLBAE learning model in thermochemical context chemistry lessons at SMAN 4 Jayapura students. The research method is the result of experimental treatment analysis which is divided into two groups (conventional control model and experiment with DLBAE model). The results of the implementation showed that the analysis test of sig (2.tailed) 0.05, indicated that there was a significant difference between the conventional model and the DLBAE model. Based on the acquisition of the average chemical value of the experimental class 77.05 from the control class 64.64. Meanwhile, the percentage of environmental literacy ability is between 80-90%. Student response to DLBAE-based thermochemistry learning was very positive. Based on the results of the analysis, the DLBAE-based learning model is very effective to use, in order to increase understanding of concepts and environmental literacy. Keywords: discovery learning, analogy, environment literacy. Abstrak: Pengaruh Pembelajaran Discovery Berbasis Analogi Lingkungan untuk Meningkatkan Literasi Lingkungan dan Pemahaman Termokimia Siswa. Penelitian ini merupakan hasil implementasi pembelajaran termokimia berdasarkan rekonstruksi model discovery learning berbasis analogy Environtment (DLBAE). Tujuan penelitian ini adalah untuk mengetahui efektifitas model pembelajaran DLBAE pada pelajaran kimia konteks termokimia pada siswa SMAN 4 Jayapura. Metode penelitian merupakan hasil analisis perlakuan secara eksperimen yang dibagi dalam dua kelompok (Kelas Kontrol dengan model konvensional, serta eksperimen dengan model DLBAE). Hasil implementasi menunjukkan uji analisis sig (2-tailed) 0,05, menunjukkan terjadi perbedaan yang signifikan antara model konvesional dan model DLBAE. Berdasarkan perolehan nilai rata-rata kimia kelas eksperimen 77,05 dari kelas kontrol 64,64. Sedangkan persentasi kemampuan literasi lingkungan berada diantara 80-90%. Tanggapan siswa terhadap pembelajaran termokimia berbasis DLBAE adalah sangat positif. Berdasarkan hasil analisis, maka model pembelajaran berbasis DLBAE sangat efektif digunakan, guna peningkatan pemahaman konsep dan literasi lingkungan.Kata kunci: pembelajaran discovery, analogi,  literasi lingkungan. DOI: http://dx.doi.org/10.23960/jppk.v11.i1.2022.01